A Subtitling Analysis On Deletion Strategy In Just Go With It Movie - Irmawati, Nova (2012)
The objectives of this study are (1) to describe the linguistic forms of deletion strategy in subtitling of Just Go with It, and (2) to describe the number of subtitlings which are equivalent and non equivalent after using deletion in subtitling of Just Go with It. In collecting of the data, the writer uses documentation method. The techniques for collecting the data are reading and selecting the data which can be categorized as deletions, classifying the linguistics form of deletion strategy, arranging the subtitling which is equivalent and non equivalent, and drawing conclusion. The collected data are analyzed by using Nida's equivalences and part of speech theory. Based on the data analysis, the writer finds the linguistic forms in Just Go with It Movie and its Subtitle. They are verb, noun, adjective, adverb, pronoun, preposition, conjunction, and interjection. The writer finds that from 150 data, there are 141 or 94% data belong to equivalent subtitle although there are strategy of deletion but the message of the SL and TL is not different contextually. And there are 9 or 6 data belong to non equivalent. So it means that the translation of Just Go with It movie and its Subtitle is good translation because thare are almost 150 data belong to equivalent translation.